How Shopee Video Stimuli Influence Impulse Purchase Intention Mediated by Pleasure - Khotimah, Kusnul; Isharina, Ikhtiara Kaideni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The growth of e-commerce in Indonesia is increasing due to the high internet usage. This phenomenon cannot be separated from the influence of people's lifestyles, including generation Z, who have a preference for making purchases online. This potential market has triggered competition between e-commerce companies in attracting consumers, especially through short videos. The SOR (Stimulus-Organism-Response) theory in this study is used to examine the effect of external stimuli in short videos such as informativeness, comments, Virtual Haptics, and price discount on impulse purchase intentions mediated by pleasure. This study uses purposive sampling method. Respondents of this study were 243 people taken from the population of generation Z Shopee video users who watched fashion products. Researchers conducted data analysis using Partial Least Square (PLS) with SmartPLS 3 software. The results showed that comments, Virtual Haptics, and price discount had a significant effect on pleasure, which in turn significantly increased impulse purchase intentions. Meanwhile, informativeness has no significant effect on pleasure.